Standardization of Growing Medium for Growth and Flowering of Alstroemeria cv. ‘Capri’ under Solan-Nauni Conditions - Negi, Rahul; Kashyap, B.; Dhiman, S. R.; Sharma, P.; Gupta, R. K. (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was carried out for two consecutive years viz., 2014-2015 and 2015-2016 at Experimental farm, Department of Floriculture and Landscape Architecture, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India to standardize growing medium for growth and flowering of Alstroemeria cv. ‘Capri’. The experiment was laid under protected condition in a completely randomized design, comprising of nine treatments with three replications each. The treatments consisted of growing media in nine different combinations i.e.; Sand+Soil+FYM (1:1:1; v/v), Sand+Soil+FYM (2:1:1; v/v), Sand+Soil+FYM (1:1:2; v/v), Sand+Soil+FYM (2:1:2; v/v), Cocopeat+FYM (1:1; v/v), Cocopeat+Soil+FYM (1:1:1; v/v), Sand+Soil+FYM (1:1:1; v/v)+Cocopeat (1:1; v/v), Sand+Soil+FYM (1:1:1; v/v)+Vermicompost (2:1; v/v) and Sand+Soil+FYM (1:1:1; v/v)+Vermicompost+Cocopeat (2:1:1; v/v). According to pooled data of these two consecutive years, growing medium consisting of Sand+Soil+FYM (1:1:1; v/v)+Vermicompost+Cocopeat (2:1:1; v/v) i.e., T9 was observed to be the best substrate for maximum plant height (123.54 cm), length of cut stem (103.83 cm), weight of cut stem (61.80 g), advanced flowering (161.83 days) and greater number of flowering stems plant-1 (34.80). Treatment T9 (vase life of 12.50 days) was also one of the most effective treatment with extended vase life as it also encouraged the growth and development of flowers. Thus, it can be concluded from the findings that treatment T9 was most effective in improving growth and flowering attributes of Alstroemeria cv. ‘Capri’.